Pemberdayaan PKK dalam Pendampingan Kelas Ibu Hamil di Desa Penyengat Olak Kabupaten Muaro Jambi - Taty Nurti; Sri Yun Utama; Ajeng Galuh Wuryandari (Jurnal Abdimas Kesehatan (JAK), 2022)
Based on information from the village midwife who is the secretary of Pokja IV PKK in Penyengat Olak Village, the problem of the pregnant women class does not work, there is no assistance for PKK cadres in the pregnant women class, and the knowledge of PKK cadres about the danger signs of pregnancy is still low, exclusive breastfeeding is still low, weighing Routinely still low, the provision of PMT does not exist, PHBS, knowledge about COVID 19, how to wash hands seven steps, Health Fund does not yet exist. / husband about health maintenance and recognizing the danger signs of pregnancy and pregnancy detection. Starting with a needs assessment carried out by a survey using a google form, then activities were carried out using the question and answer method, lectures, brainstorming, and the practice of pregnant exercise using pocketbooks and audiovisual media. By providing knowledge and increasing awareness and motivation of cadres to assist pregnant women, activities for pregnant women can be carried out during a pandemic by implementing health protocols.